Methods of test for rubber and plastics hoses and hose assemblies Part 102. Hydraulic pressure tests Sec 102.8 Pressure impulse test for rigid helix reinforced thermoplastics hoses (BSI, 1987)
Flexible pipes, Pipes, Natural rubber, Synthetic rubber, Plastics, Reinforced materials, Pressure testing, Hydraulic tests, Mechanical testing, Polymers, Test equipment, Specimen preparation, Thermoplastic polymers, Testing conditions, Helical shape, Pressure pipes